Experience of operation of electronic database of full-text standards HAMMER in PJSC "Ukrtransgaz" - I. Trebulova, G. Kogut, A. Klyun, M. Karpash (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2018)
In the article, the mechanism of effective normative document provisioning is comprehensively studied, statistical studies on the use of various NDs types in the Company are analyzed; the indicators of the priority use of NDs are analyzed; development and improvement trends of the regulatory base for gas transmission industry of Ukraine following the abolition of the standards of the former USSR and the introduction of modern European and international standards in Ukraine are highlighted. The aim of this study is to represent the results of implementation of an electronic data-retrieval system of full-text operating normative documents in PJSC “Ukrtransgaz”, emphasizing on the necessity of upgrading the existing normative documents. The paper demonstrates a relatively new approach to management of standards necessary for operation of a big service provider in the gas supply sector of Ukraine.